Professional pedagogical guidance for the formation of professional pedagogical interests in the University College - Pirez Enriquez, Yudisleidys; Cabanes Flores, Lida; García Ruiz, Jorge (Transformación, 2024)
Objective: This article aims at describing a model to promote professional pedagogical motivation in prep students by means of professional pedagogical orientation.  Methods: The authors rely on theoretical level methods such as analysis-synthesis, induction-deduction, modeling and the functional structural systemic method; at well as on documentary analysis, observation, interview, the questionnaire, Iadov's logical table, composition and sentence completion of an empirical level nature.  Result: The main finding is a theoretical construction that represents the process leading to professional pedagogical motivation in prep students resulting from professional pedagogical orientation. Conclusion:  Professional pedagogical interests arising may result from a professional orientation characterized by coherent convergence of training influences consonant with students’ performance at the prep corresponding to knowledge and representations about doing and affections. In such a way that students express a stable tendency to the profession cognitive approach to the profession and a relatively constant positive move towards pedagogical activity.
Keywords: teacher education; teacher motivation; teacher orientation; vocational guidance